To set Mail Screening Facilities into Uzbekistan Postal System (Eurasian Journal of Research, Development and Innovation, 2023)
The purpose of this thesis is to indicate an establishment of the most effective and sophisticated Screening Mail System in Uzbekistan Postal System. The information in this thesis is really sufficient to build the security system. I will provide with some Primary Categories of Mail Screening and Sorting Facilities below. I divided the facilities into 5 categories: offsite Screening Facilities / Remote Delivery Sites, Isolated On-Campus Facilities, Primary Office Locations, Single Room Mail Center Operations and Mail Screening Facility Core Requirements. We can look at them detailed below